2021
DOI: 10.3934/publichealth.2021053
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 pandemic containment in the Caribbean Region: A review of case-management and public health strategies

Abstract: <abstract> <p>COVID-19 emerged initially from Wuhan, Hubei province, China, in late December 2019, and since then, it has spread globally to be declared a pandemic by the World Health Organization. The Caribbean region started reporting COVID-19 cases in early March 2020, triggering new regional public health crises. The initial suspects and confirmed cases across the Caribbean countries were mainly imported cases and from cruise ships. The clinical manifestations varied from fever, cough, and mala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 58 publications
1
12
0
Order By: Relevance
“…Low HL, mental stress, poor life satisfaction and an unhealthy diet are significantly associated with serious negative health outcomes 34 35. Based on the global health indices, the best-performing countries in combatting the ongoing COVID-19 pandemic have been those with smaller population, higher government funding allocation towards healthcare and those having robust public governance 36. The current study aims to investigate adherence to COVID-19 prevention measures and willingness to vaccinate against COVID-19, in relation to HL, perceived stress, life satisfaction and other participant’ sociodemographic and lifestyle characteristics, among the adult German population.…”
Section: Introductionmentioning
confidence: 99%
“…Low HL, mental stress, poor life satisfaction and an unhealthy diet are significantly associated with serious negative health outcomes 34 35. Based on the global health indices, the best-performing countries in combatting the ongoing COVID-19 pandemic have been those with smaller population, higher government funding allocation towards healthcare and those having robust public governance 36. The current study aims to investigate adherence to COVID-19 prevention measures and willingness to vaccinate against COVID-19, in relation to HL, perceived stress, life satisfaction and other participant’ sociodemographic and lifestyle characteristics, among the adult German population.…”
Section: Introductionmentioning
confidence: 99%
“…92,159 The generally favorable attitude towards COVID-19 vaccine acceptance might have contributed to generally high vaccine coverage observed in the Caribbean. 160 Fifth, several MENA region countries reported very low levels of COVID-19 vaccine acceptance (with six countries ranked among the top 10 countries with regard to COVID-19 vaccine hesitancy among the countries included in this review). This result was previously reported in an earlier systematic review that reported COVID-19 vaccine acceptance rates by the end of December 2020 and is further supported by the observations made in this review.…”
Section: Dovepressmentioning
confidence: 98%
“…These are Pfizer which is an mRNA subtype vaccine, AstraZeneca is an adenovirus subtype 29 and Sinopharm is an inactivated whole virus subtype. 30 COVID-19 vaccination coverage varies significantly between countries reaching high percentages up to 86.2% in Sint Maarten 31 and 97.9% in United Arab Emirates and as low as 0.1% in Burundi. 32…”
Section: Discussionmentioning
confidence: 99%